The Effectiveness of Competency-Based Performance Management on Employee Productivity with Organizational Commitment as a Mediation Variable in the Banking Industry - Vibry Puspitasari; Sutianingsih, Sutianingsih (Cita Konsultindo Research Center, 2025)
This study aims to examine the impact of service ability and communication ability on employee productivity, with work commitment as an intermediary variable. The research sample consisted of 115 employees of PT BPR Bank Djoko Tingkir Sragen. This study uses census techniques to obtain data from all members of the population. The data collected through the questionnaire were then analyzed by data analysis techniques such as validity tests, reliability, classical assumption tests, and multiple linear regression analysis along with their supporting tests such as the determination coefficient test, f test, t test, and sobel test. Based on the results of data analysis, it can be concluded that service skills and communication skills have a very important impact on organizational commitment. Service skills, communication skills, and organizational commitment have a very important contribution to employee productivity. The organization's commitment mediates service capabilities and communication skills to employee productivity at PT BPR Bank Djoko Tingkir Sragen. Keywords: management effectiveness, organizational commitment, employee productivity